PENGARUH STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT FAJAR MITRA KRIDA ABADI KEBAYORAN BARU JAKARTA SELATAN - Dwi Santoso; Muhammad Gandung (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of the work environment (X1) and work discipline (X2) on employee performance (Y). Based on the results of the analysis using SPSS version 27, the work environment variable (X1) partially has a significant influence on employee performance (Y) with a t value of 5.248, greater than the t table of 2.006, and a significance level of 0.011 (<0.05) . The work discipline variable (X2) also shows a partially significant influence on employee performance (Y), with a calculated t of 3.490, greater than t tablet of 2.006, and a significance level of 0.000 (<0.05). Simultaneously, the work environment (X1) and work discipline (X2) have a significant influence on employee performance (Y) as shown by the results of multiple linear regression Y=4.755+0.548(X1)+0.342(X2)Y = 4.755 + 0.548(X_1 ) + 0.342(X_2)Y=4.755+0.548(X1)+0.342(X2). The calculated f value of 336.894 is greater than the table f of 3.17, so Ha is accepted. The correlation coefficient (R) of 0.210 and the adjusted coefficient of determination (R2) of 0.013 indicate that the work environment and work discipline simultaneously contribute 80% to employee performance, while the remaining 20% ​​is influenced by other variables not studied. This research concludes that either partially or simultaneously, the work environment and work discipline have a significant influence on improving employee performance at PT Fajar Mitra Krida Abadi.